(untitled) (Journal of Foreign Language Studies, 2020)
Japanese language has a diverse and complex writing system in which Kanji accounts for about 70%. Nowadays, there have been many studies on Japanese language in various aspects, but those related to teaching and learning Kanji remain very limited. Especially, in Vietnam, there is a lack of research on Kanji teaching and learning methods. This article deals with difficulties in teaching and learning Kanji with the Japanese coursebook Minna no Nihongo at Hanoi University, then proposes improvements in the use of software and flipped learning to improve the effectiveness of teaching and learning Japanese Kanji.